A New Counter-Etch Solution for Corrections on Zinc Printing Plates - Obana, Mitsuo (The International Hydrographic Review, 2015)
Nautical charts must be kept up-to-date in order to provide navigators with the latest information. Both chart printing plates and film negatives have therefore to be continually updated by means of corrections. Before making a correction the zinc plates used by the Hydrographic Department of Japan are treated with a counter-etch solution and a polishing stick to remove the obsolete images and clean the plate. New printing images are then drawn in by hand or printed by photomechanical process. The result obtained depends on the quality of the counter-etch solution; the new image must be sufficiently bold and distinct. The solution hitherto used was somewhat ineffective, in that the corrected images on the plate were often insufficiently clear, and the oil-sensitivity of the plate deteriorated during printing, causing the printing ink to lose adhesion so that sometimes breaks or omissions in reproduction occurred. In order to remedy this deficiency, a counter-etch solution with better properties was sought and finally devised.